The development of results in 100m and 400m sprint races in athletes aged from 6 to 100 - Iskra, J.; Pietrzak, M.; Szczesna, M.; Gwiazdon, P. (Journal of Physical Education & Health, 2016)
The 100 m race is not only a sports discipline but also a way of assessing an athlete`s speed abilities. The run over the distance of 400 metres combines both speed and endurance (anaerobic) capacities. The purpose of the study was to evaluate the development of results in men's 100 and 400m sprint races, taking into account the best performance within the age from 6 to 100. By examining the course and the development of the world's leading sprinters` careers, the authors took into consideration their best final results achieved each year. They were assigned to three research protocols that included age, successive years of starts, and the period before and after their personal best.The results are presented with arithmetic means and standard deviations (SD). In the comparative analysis of groups of runners over various distances (100 and 400m), the percentage value (%) of the result in relation to the world record over the given distance was chosen as a common element. The research has shown that the age range from 20 to 31 in the 100m race and 20 to 29 in the 400m run respectively, are the best periods for continuation of a sports career suitable for the shortest and longest sprint distance at the highest world level. The development of speed abilities up to the age of 14 is similar to the scale of their regression after the age of 35. Knowledge concerning the change in sports performance level in relation to age provides the opportunity to predict the periods of peak performance in a given sports discipline. This enables a rational and proper planning of the training process.